Improve the Positioning Accuracy for Indoor Applications Based on Hyperbolic Method with Optimum Measurement - Noor N. Abed; Mahmood F. Mosleh; Faeza A. Abed; Ali A. Abdullah; Atta Ullah (Journal of Techniques, 2023)
The localization for indoor environments is faced by problems related to high error rates. To address this problem, a hyperbolic method is chosen which is a suitable for such environments. Also, such methods give a significant error when depending on RSS values, which suffer from unstable reading. To overcome this phenomenon, a proposed method is presented in this research to choose a suitable value of RSS. The idea is to install 4TXs in the chosen case study building and select the best two reading of 2TXs lying on the same side of the square case study building among four values of RSS measured from the 4TXs. The results show that, a significant reduction of error is achieved using the proposed method as the range of achieved error is between (0.1091, 0.0061) to (1.7162, 1.6593). While, the such range are from (0.0114, 0.0472) to (1.2685, 2.3207) by using 2TXs. Finally, a validation of achieved error is applied for the results of proposed method applied by real measurements. The results of such validation show that a close measurement to the simulation result is achieved.